P Peran Media Sosial Terhadap Manajemen Krisis Public Relations “PT Indonesia Bakery Family” Pada Roti Aoka: Peran Media Sosial Terhadap Manajemen Krisis Public Relations “PT Indonesia Bakery Family” Pada Roti Aoka - Syihabuddin, Muhammad (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2024)
Media serves as both a challenge and an essential tool for branding and information management for companies, institutions, and individuals. For public relations professionals, social media can become a starting point for a crisis if not effectively managed. This study explores the role of social media in crisis management, particularly regarding the impact of apologies on public sentiment post-crisis. Crises can arise unexpectedly and require management that is prepared to address issues that attract public attention. PT Indonesia Bakery Family (IBF) faced a crisis when its product, Roti Aoka, was accused of containing sodium dehydroacetate, a substance commonly used in cosmetics. This research analyzes the steps taken by PR IBF in addressing this crisis through three stages of crisis management: pre-crisis, crisis, and post-crisis.